Microsatellite instability and mutational analysis of transforming growth factor β receptor type II gene (TGFBR2) in sporadic ovarian cancer. Issue 4 (1st August 2001) - Alvi, A J; Rader, J S; Broggini, M; Latif, F; Maher, E R
Abstract : Aims —To investigate the possible role of mutations in the transforming growth factor β receptor type II gene (TGFBRII) in ovarian cancer and its relation to microsatellite instability (MSI), 43 sporadic ovarian tumours were analysed for mutations over the entire coding region of the TGFBRII gene. Methods —Mutational analysis was performed using the polymerase chain reaction (PCR), single strand conformation polymorphism (SSCP) gel analysis, and direct sequencing. MSI analysis included both mononucleotide and dinucleotide microsatellite markers used for radiolabelling and gene scanning. Results —No pathogenic mutations were detected, although sequencing of the polyadenine (poly A) tract in exon 3 using conventional techniques revealed a spurious frameshift mutation that was not present in the same samples analysed using a proofreading Taq polymerase. MSI analysis demonstrated an MSI negative phenotype in 40 of the 43 tumours. None of the three MSI positive tumours demonstrated MSI for mononucleotide markers only. Conclusions —These findings suggest that: (1) MSI (both conventional and mononucleotide) is infrequent in ovarian cancer and (2) inactivation of the MSH2, MLH1, and MSH6 mismatch repair genes and TGFBR2 gene mutations do not play a major role in ovarian cancer tumorigenesis. The spurious TGFBR2 frameshift mutations detected by sequencing after conventional PCR underline the importance of confirming putative mutations in repetitive sequences by alternative methods.